Factors that facilitate the adoption of a frame saws like a forestry logging technology: case studies with producers that manage communal forests - Posas Guevara, Ana L. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. sc) -- CATIE, Turrialba (Costa Rica), 1998